Protection and Control of the State Border as a Component of Ensuring National Security of Ukraine - V. V. Polovnikov (Bulletin of Kharkiv National University of Internal Affairs)
The issues of borders and national foundations of state formation are of great importance in Ukraine. Ukraine is developing within the existing borders on the basis of use by the Ukrainian nation of its inalienable right for self-determination, provides the safeguard and protection of the national statehood of the Ukrainian people, and takes the lead on its territory. The inviolability of the territory of Ukraine within the existing borders implies the inviolability of these borders.